Comparative Pharmacodynamics and Pharmacokinetics of Oral Direct Thrombin and Factor Xa Inhibitors in Development - Eriksson, Bengt I.; Quinlan, Daniel J.; Weitz, Jeffrey I. (Clinical pharmacokinetics, 2009)
For the past five decades, there has been little progress in the development of oral anticoagulants, with the choices being limited to the vitamin K antagonists (VKAs). The situation is changing with the development of orally active small molecules that directly target thrombin or activated factor X (FXa). The two agents in the most advanced stages of development are dabigatran etexilate and rivaroxaban, which inhibit thrombin and FXa, respectively. Both are approved in the EU and Canada for venous thromboprophylaxis in patients undergoing elective hip- or knee-replacement surgery. Other agents in the early stages of development include several FXa inhibitors (apixaban, DU 176b, LY 517717, YM 150, betrixaban, eribaxaban [PD 0348292] and TAK 442) and one thrombin inhibitor (AZD 0837). With a predictable anticoagulant response and low potential for drug-drug interactions, these new agents can be given in fixed doses without coagulation monitoring. This renders them more convenient than VKAs. While the anticoagulant effect of the new thrombin and FXa inhibitors is similar, differences in the pharmacokinetic and pharmacodynamic parameters may influence their use in clinical practice. Here, we compare the pharmacokinetic and pharmacodynamic features of these new oral agents.